Moringa and its Health Significance - Hamdard, Mohammad Hamid (Journal of Natural Sciences – Kabul University, 2020)
Moringa oleifera, a member of the Moringaceae family, is a fast-growing plant originally from Asia but now widely available in tropical and subtropical regions. It holds great economic importance in both the food and medicinal industries. Some people use this plant as food, while its seeds are a rich source of oil and protein. Moringa is also utilized for water purification. Various parts of the plant, including the leaves, seeds, bark, roots, sap, and flowers, are used in traditional medicine. Moringa oleifera leaves contain significant amounts of crude protein, and immature seed pods are also used in human nutrition.